The empirical evaluation of productivity growth and efficiency of LSEs in the Malaysian food processing industry - Yodfiatfinda,; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Hussein, Md. Ariff; Yusop, Zulkornain; Radam, Alias (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
This study investigates productivity growth and efficiency of Large Scale Enterprises (LSEs) in the Malaysian food processing industry. Malmquist productivity index of Data Envelopment Analysis (DEA) was employed to five-digit panel data for the period of 2000-2006. The findings suggest that average Technical Efficiency (TE) of the LSEs was 0.683 during the period of observation, which indicates that the industries are able to expand their output as much as 31.7 percent by using the same level of inputs. Total Factor Productivity (TFP) growth was positive at 7.3 percent, which is contributed by a Technical Efficiency Change (EFCH) of 4.3 percent and Technological Change (TECH) of 3.0 percent. Sub industries of manufacturing alcohol and wine as well as the processing and preserving of meat and meat products shows the highest productivity growth at 84.8 percent and 47.5 percent respectively. On the other hand, the sub industries of processing and preserving poultry and poultry products together with the manufacturing of chocolate are those which have the lowest TFP growth at -30.5percent and -14.8 percent respectively. The significant determinants of the productivity growth, with a positive relationship are public infrastructure, IT expenditure and foreign ownership, while energy price is the determinant with a negative relationship. The main contributor to the TFP growth of the LSEs in the Malaysian food processing industry is EFCH, however, the LSEs can also improve the TFP growth by moving forward the production frontier as well.